Teologi Filantropi Perspektif Buya HAMKA - Muhammad Dwifajri (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
This study discusses the idea of HAMKA on the relationship between aqidah and philanthropy. As understands that Islam has four aspects; aqidah, ibadah, and mu’amalah and akhlak. Thoses aspects are inseparable. The purpose of the study is to argues that aqidah and philanthropy are also inseparable. This study applies a qualitative approach, based on literature review. Strictly speaking, in this context, aqidah (belief / faith) is closely related to action, including in philanthropic practice. According to HAMKA, faith must be proved in action and philanthropy activity to those are in need is manifestation of faith